2015
DOI: 10.1590/0001-3765201520140461
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors related to the production of a complex set of spicules in a tropical freshwater sponge

Abstract: Adverse natural conditions will, generally, induce gemmulation in freshwater sponges. Because of this environmental dependence, gemmoscleres are given exceptional value in taxonomic, ecological and paleoenvironmental studies. Other spicules categories such as microscleres and beta megascleres have received little attention with regard to their occurrence and function during the sponge biological cycle. Metania spinata, a South American species common to bog waters in the Cerrado biome, produces alpha and beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The Si/Al values decrease after 75 cm would be related to less winter precipitation and therefore a reduced water input from the river and/or the watershed. Calm water conditions were favourable expansion of benthic diatoms, mainly Surirella, a genus that lives in shallow environments with high silica requirement (Matteuzzo et al, 2015). The predominance of benthic diatoms in the assemblage for the upper part of the core (Figure 6), added to sedimentological changes (Figure 2), could corroborate a main tectonic control, with lesser climatic control reflected in discrete variations in the relative abundance of benthic diatoms and the sudden occurrence of Aulacoseira spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Si/Al values decrease after 75 cm would be related to less winter precipitation and therefore a reduced water input from the river and/or the watershed. Calm water conditions were favourable expansion of benthic diatoms, mainly Surirella, a genus that lives in shallow environments with high silica requirement (Matteuzzo et al, 2015). The predominance of benthic diatoms in the assemblage for the upper part of the core (Figure 6), added to sedimentological changes (Figure 2), could corroborate a main tectonic control, with lesser climatic control reflected in discrete variations in the relative abundance of benthic diatoms and the sudden occurrence of Aulacoseira spp.…”
Section: Discussionmentioning
confidence: 99%
“…DZ2a corresponds to an oligosaprophic, oligotrophic, very low alkalinity and calm conditions. The presence of gemmosclere and microsclere sponge spicules (<20%) observed between 70 and 80 cm is associated to seasonal fluctuations in lake level and high concentration of dissolved Si (Matteuzzo et al, 2015). The presence in sample DZ2b 55–65 cm of Aulacoseira records more turbid conditions due to sudden detrital inputs and nutrient availability in the lake.…”
Section: Discussionmentioning
confidence: 99%
“…In a generic context, there was a survey of the sponges assembly in the Central Amazon, where they were characterized by habitats (Batista et al 2003). Also noteworthy are studies on sponges as bioindicators of some coastal environments in South America (Volkmer-Ribeiro & Machado 2007), and with environmental factors related to the production of a complex set of spicules (Matteuzzo et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Both, surface sediment spicules (Łukowiak, Pisera & O'Dea, 2013) and spicules from assemblages of coralligenous conglomerates (Bertolino et al, 2014(Bertolino et al, , 2017a(Bertolino et al, , 2017b(Bertolino et al, , 2019 were shown to reflect the living sponge communities to a good degree of accuracy and can be used, with some cautions, for reconstructing former sponge communities. In turn, Matteuzzo et al (2015) investigated the factors that influence the formation of spicules in freshwater sponges. They showed that the sequential production of a complex set of spicules (alpha megascleres followed by microscleres, gemmuloscleres and beta megascleres) in the neotropical freshwater sponge Metania spinata depends on the water level, temperature, and silicon concentration.…”
Section: Termmentioning
confidence: 99%